Performing Arts Center - William B. Dewey::::::::: (2000)
An aerial view from May 2000 of the Performing Arts Center's Christopher Cohan Center. Opened in 1996, the PAC was funded by a partnership among Cal Poly, the city of San Luis Obispo, and the Foundation for the Performing Arts.